Beyond the line: Carl Schmitt and the constitutive outsider of the international. (May 2019) - Yamato, Roberto Vilchez
In this article, I offer a reading of the pirate in Carl Schmitt inspired by Reinhart Koselleck's study on asymmetric counterconcepts. I argue that the pirate in Schmitt marks a negative asymmetric counterconceptual position associated with a space of exception in relation to which one may also identify the outlaw enemy of humanity. In displacing the political and mapping the pirate's position within Schmitt's conceptual order, the significance of this article's main contribution is to draw attention to a specific asymmetric counterconceptual structuring that marks the limits of 'our' international political world with the dehumanized negativity of its constitutive outsider. Rereading Koselleck's methodological qualification on the structural iterability of asymmetric counterconcepts, the article suggests that the spectre of the pirate lives on, haunting the outer limits of the international and legitimizing abject forms of violence.